Given  `A= ((4, 3, 2),(5,6,3),(3,5,2));B = ((a, b, c),(d,e,f),(g,h,i))`

Find B so that  AB = I = BA as follows:

First equate entries on the two sides of the equation AB = I . Then solve the resulting nine equations for a, b, c, d, e, f, g, h and i.

Expert Answers

An illustration of the letter 'A' in a speech bubbles

You need to multiply the matrices A and B such that:

`((4,3,2),(5,6,3),(3,5,2))*((a,b,c),(d,e,f),(g,h,i)) = ((1,0,0),(0,1,0),(0,0,1))`

`((4a+3d+2g, 4b+3e+2h, 4c+3f+2i),(5a+6d+3g, 5b+6e+3h, 5c+6f+3i),(3a+5d+2g, 3b+5+2h, 3c+5f+2i)) = ((1,0,0),(0,1,0),(0,0,1))`

Equating corresponding terms yields:

`4a+3d+2g = 1 `

`4b+3e+2h = 0`

`4c+3f+2i = 0 `

`5a+6d+3g = 0 `

`5b+6e+3h = 1 `

`5c+6f+3i = 0 `

`3a+5d+2g = 0 `

`3b+5e+2h = 0 `

`3c+5f+2i = 1`

You need to consider the equations that contain a,d,g such that:

`4a+3d+2g = 1 `

`5a+6d+3g = 0 `

`3a+5d+2g = 0`

You need to subtract the third equation from the first such that:

`a - 2d = 1`

You need to multiply the first equation by 3 and the second equation by -2 and then you should add the new equations such that:

`12a + 9d + 6g = 3`

` -10a - 12d - 6g = 0`

`2a - 3d = 3`

You need to multiply the equation a - 2d = 1 by -2 such that:

`-2a + 4d = -2`

Adding this equation to 2a - 3d = 3 yields:

`2a - 3d - 2a + 4d= 3 - 2`

`d = 1 =gt a - 2 = 1 =gt a = 3`

`15+6+3g = 0 =gt 3g = -21 =gt g = -7`

You need to consider the equations that contain b,e,h such that:

`4b+3e+2h = 0 `

`5b+6e+3h = 1 `

`3b+5e+2h = 0`

Subtracting the third equation from the first yields:

`b - 2e = 0 =gt b = 2e`

Substituting 2e for b in the first and second equations yields:

`11e + 2h = 0 `

`16e + 3h = 1`

You need to multiply by 3 the equation 11e + 2h = 0 and by -2 the equation 16e + 3h = 1 such that:

`33e + 6h = 0 `

`-32e - 6h = -2`

`33e + 6h -32e - 6h = 0-2`

`e = -2 =gt b = -4`

`-16-6+2h = 0 =gt 2h = 22 =gt h = 11`

You need to consider the equations that contain c,f,i such that:

`4c+3f+2i = 0 `

`5c+6f+3i = 0 `

`3c+5f+2i = 1`

`4c+3f+2i - 3c-5f-2i = -1`

` c - 2f = -1 =gt c = 2f - 1`

Substituting 2f - 1 for c in the first and second equations yields:

`4(2f-1)+3f+2i = 0=gt 11f + 2i = 4 `

`5(2f-1)+6f+3i = 0 =gt 16f + 3i = 5`

`3(11f+2i) - 2(16f+3i) = 12 - 10`

`33f + 6i - 32f - 6i = 2`

`f = 2 =gt c = 4 - 1 = 3`

`12+6+2i = 0 =gt 2i = -18 =gt i = -9`

Hence, evaluating the matrix B under given conditions yields `B = ((3,-4,3),(1,-2,2),(-7,11,-9)).`

See eNotes Ad-Free

Start your 48-hour free trial to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Get 48 Hours Free Access
Approved by eNotes Editorial